DEVELOPMENT OF DRYING PROTOCOL FOR WITHANIA SOMNIFERA ROOTS - S, Soni; Chawra, Himmat Singh; Rk, Sharma; R, Garg (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This experiment was conducted to develop a drying protocol for Withania somnifera roots (during the year 2009–2010 under the National Medicinal Plants Board project, B.R. Nahata College of Pharmacy-Scientific Institute of Research Organization, Mandsaur [M.P.]). Methods: The roots of Withania were harvested and cut into different sizes (2–4 inches) and subjected into sun drying, shade drying, and hot air oven drying in temperature ranging from 40°C to 60°C. The temperature for sun drying ranging from 32°C to 42°C during daytime, and in night hours, the samples were kept in plastic covers to prevent reabsorption of moisture. In shade drying, the pieces of roots were kept in shade (proper air flowing place) at normal climatic temperature. Moreover, in hot air oven drying method/mechanical drying method, the pieces of roots were kept at 50°C, 55°C, and 60°C, respectively. The samples were weighed, and the moisture content of the samples was taken at regular intervals until the standard moisture content of the dried roots was obtained that is mentioned in literature (10–5%). Result: The result revealed that hot air oven drying of roots took the lowest time (12 h), while sun drying method took 24 h for drying. The alkaloid content, namely, Withanolide A was significantly influenced by different methods of drying. The highest alkaloid content (0.010%) was observed in sun drying and hot air oven drying with 0.021.abc% as compared to shade drying with 0.009% Withanolide A. Conclusion: It may be concluded that sun drying and hot air oven drying are suitable methods for drying W. somnifera roots.